2005
DOI: 10.1108/01437730510582554
|View full text |Cite
|
Sign up to set email alerts
|

The influence of superleader behaviors on organization commitment, job satisfaction and organization self‐esteem in a self‐managed work team

Abstract: PurposeThe purpose of this paper was to examine the impact of superleader behaviors in self‐managed work teams, on organization commitment, job satisfaction and organization self‐esteem.Design/methodology/approachData were collected on‐site over a period of three days from employees working in a non‐union paper mill located in a small rural community in the northwestern region of the USA. The survey was completed by 141 employees, representing a 9 per cent response rate. Self‐leadership, organization commitmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
(41 reference statements)
4
32
0
2
Order By: Relevance
“…Thus, it is not surprising that several investigators have studied predictors of job satisfaction among health‐care staff, and in particular nurses (Loke , Meyer & Herscovitch , Elloy , McGlynn et al . ).…”
Section: Overview Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not surprising that several investigators have studied predictors of job satisfaction among health‐care staff, and in particular nurses (Loke , Meyer & Herscovitch , Elloy , McGlynn et al . ).…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…Thus, it is not surprising that several investigators have studied predictors of job satisfaction among health-care staff, and in particular nurses (Loke 2001, Meyer & Herscovitch 2001, Elloy 2005, McGlynn et al 2012. These investigators have shown that job satisfaction is influenced by organisational commitment, perceived organisational support, leadership behaviour, level of education (Loke 2001, Yoon & Thye 2002, Freund 2005 and professional commitment (Lu et al 2002(Lu et al , 2007, as well as job stress (Wagner & Huber 2003) and work value (Taris & Feij 2001, Hegney et al 2006.…”
Section: Job Satisfactionmentioning
confidence: 99%
“…A transformation leader's consideration for followers' individuality and willingness to coach them do, in fact, create meaningful exchanges (Lee, 2005). Teams that are led by a supervisor who exhibits the characteristics of a super leader also have higher levels of organisational commitment (Elloy, 2005). Joiner and Bakalis (2006) report that strong co-worker and supervisor support contributes to affective commitment.…”
mentioning
confidence: 99%
“…Verplaken (2003) found value congruence and shared emphasis on human relations value facilitated job satisfaction perceptions of nurses. Elloy's (2005) research suggests leader behaviors contribute to perceptions of job satisfaction, while the work of Gidron (1986) and Yiu et al (2001) suggest both content (i.e., work related variables) as well as context (i.e., work environment variables) contribute to volunteer or unpaid staff member perceptions of job satisfaction. Specifically, Gidron (1986) found lack of stress, the work itself, and feelings of task achievement predicted job satisfaction while, Yiu et aI.…”
Section: Job Sati4actionmentioning
confidence: 99%
“…In the following investigations, we will focus on the relationship between commitment, job satisfaction, and organizational member effort (Testa, 2001) and the influence of leader behaviors on organizational commitment (Elloy, 2005). …”
Section: Job Sati4actionmentioning
confidence: 99%